Pilot test za implementaciju programa precizne zdravstvene njege kod pacijenata sa dijabetesom u Indoneziji - Pranata, Satriya; Wu, Shu-Fang Vivienne; Wang, Tsae-Jyy Tiffany; Liang, Shu-Yuan; Bistara, Difran Nobel; Chuang, Yeu-Hui; Lu, Kuo-Cheng; Atmaja, Hadi Kusuma (Scripta Medica, 2023)
Background/Aim: An evaluation of precision healthcare interventions among patients with diabetes in a small sample through a pilot test before being tested in a larger sample is needed. Thus, the purpose of this study was to evaluate the feasibility of a precision healthcare program. It also assesses the program’s outcome among patients with diabetes in Indonesia. Methods: Data were collected during December 2020. The researchers first gathered data about participant characteristics. Furthermore, the strategies of precision healthcare were implemented in sixty respondents to evaluate the feasibility and outcome of the program in a month. Results: The participants mention that they can follow all procedures of precision healthcare. However, they asked the researcher to provide a guide and monitoring book which provides safe choices information on diet, exercise, glucose monitoring and drug medication. Moreover, participants mentioned that they could complete all questionnaires but needed a company of a research assistant. The benefits of a month of precision healthcare were improved diabetes self-care activity, blood pressure and blood glucose level. However, the body weight, body mass index (BMI), triglyceride, cholesterol and triglyceride glucose index were not significantly improved. Conclusion: A pilot test is needed to ensure the feasibility of the implementation strategy with the culture and background of diabetic patients in Indonesia. Improving diabetes self-care activity stabilised blood pressure and blood glucose during a month, so it can be assumed that precision healthcare approaches were potentially being applied in Indonesia. On the other hand, it is needed more than a month to improve body weight, body mass index (BMI), triglyceride, cholesterol and triglyceride glucose index. Thus, testing the precision healthcare approach in a larger sample with long time series for patients with diabetes in Indonesia through a randomised controlled trial (RCT) is needed.